Evaluation of quantitative head impulse testing using search coils versus video-oculography in older individuals - Agrawal, Yuri; Schubert, Michael C; Migliaccio, Americo A; Zee, David S; Schneider, Erich; Lehnen, Nadine; Carey, John P (Otology & neurotology, 2014)
To evaluate the validity of 2D video-oculography (VOG) compared with scleral search coils for horizontal AVOR gain estimation in older individuals. Cross-sectional validation study. Tertiary care academic medical center. Six individuals age 70 and older. Simultaneous eye movement recording with scleral search coil (over right eye) and EyeSeeCam VOG camera (over left eye) during horizontal head impulses. Best estimate search coil and VOG horizontal AVOR gain, presence of compensatory saccades using both eye movement recording techniques. We observed a significant correlation between search coil and VOG best estimate horizontal AVOR gain (r = 0.86, p = 0.0002). We evaluated individual head impulses and found that the shapes of the head movement and eye movement traces from the coil and VOG systems were similar. Specific features of eye movements seen in older individuals, including overt and covert corrective saccades and anticompensatory eye movements, were captured by both the search coil and VOG systems. These data suggest that VOG is a reasonable proxy for search coil eye movement recording in older subjects to estimate VOR gain and the approximate timing of corrective eye movements. VOG offers advantages over the conventional search coil method; it is portable and easy to use, allowing for quantitative VOR estimation in diverse settings such as a routine office-based practice, at the bedside, and potentially in larger scale population analyses.